(untitled) (KULT_online, 2022)
The edited volume Transitzonen zwischen Literatur und Museum (eds. Matteo Anastasio and Jan Rhein) introduces a wide spectrum of interdisciplinary and intermedial approaches to how literature and museums can intertwine, reflect upon, and enrich each other. It explores the meanings as well as potential of such convergences from the perspectives of both literary narrative and museum practices. As such, the book presents a valuable contribution to literary, cultural, media, and museum studies.